Does foreign direct investment harm the environment in developing countries? Dynamic panel analysis of Latin American countries - Jungho Baek; Yoon Jung Choi; Wing-Keung Wong (Economies, 2017)
This article sets out to study the FDI-environment nexus within a dynamic panel data framework. To that end, the pooled mean group (PMG) method of Pesaran et al. (1999) is used to assess the impact of FDI on CO2 emissions, controlling for income and energy consumption, using a panel of 17 Latin American countries. Our results using the full sample show that FDI increases CO2 emissions, confirming the pollution haven hypothesis. But when splitting the data into different income groups, FDI inflows only in high-income countries increase CO2 emissions. In addition, CO2 emissions with growth tend to increase monotonically within the full sample and middle-income countries. Finally, energy consumption is found to increase CO2 emissions in all cases: the full sample, high-, middle- and low-income countries.
Keywords: C23; F18; 330; CO2 emissions; FDI; Latin America; panel analysis; PMG